Solow-Swan Model of Economic Growth with Allee Effect - Kseniya Akhalaya; Vladimir Shikhman (Journal of Quantitative Economics, 2025)
Abstract In this paper we expand the neoclassical Solow-Swan model of economic growth by introducing population dynamics with Allee effect. Allee effect implies the existence of a threshold for the viability of populations, i.e. a population below this threshold decreases. Above the threshold, the population gradually saturates. We show that the corresponding capital stock per capita may stabilize at two different levels. Both can be expressed in terms of equilibrium points of the standard Solow–Swan model with particular constant population growth rates. Surprisingly enough, the capital stock per capita performs in the long run better if the population becomes extinct, rather then it advances the saturation level. For this conclusion the decrease of population should be relatively moderate compared to the capital depreciation.
Additional information: C62;O40
Keywords: 330; Economic growth; Solow-Swan model; Allee effect; Capital stock per capita